Assistance algorithm of nursing for amiodarone intravenous infusion - Francimar Tinoco de Oliveira; Graciele Oroski Paes; Maria Gefé da Rosa Mesquita; Victor Magalhães de Paula Souza; Elaine dos Santos Carlos; Caroline Scantamburlo Martins (Rev Rene)
This study aimed at identifying scientific publication on phlebitis caused by amiodarone and proposes a nursing care algorithm for interventions in intravenous amiodarone administration grounded in the Infusion Nursing Society and the Center for Disease Control and Prevention. It is a descriptive study mediated by integrative review in MedLine, LILACS, IBECS, BDENF, Cochrane Library and Scielo bases, published from 2006 to 2013. The sample consisted of nine articles. The evidence pointed the incidence of phlebitis due to the infusion of amiodarone and the need to control this event. The algorithm proposed shows the materials to be used and the procedure of drug administration in order to minimize injury. Besides subsidizing the development of future studies, this algorithm also promotes the incorporation of the best recommendation for the interventionist clinical practice.